Photoinitiator-loaded up-conversion MOFs composite material for near-infrared light curing and preparation method of photoinitiator-loaded up-conversion MOFs composite material
Through the design of UCPs@MOFs composite particles, the photoinitiator is loaded with MOFs to shorten the distance between the photoinitiator and UCPs, and improve the upconversion luminescence utilization rate, solving the problem of low luminescence efficiency of upconversion particles and achieving faster photopolymerization Rate and higher material properties are suitable for fields such as 3D printing.
Patent Information
- Application Number
- CN202411235373.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-04
AI Technical Summary
The low luminescence efficiency of upconverted particles UCPs limits the application of near-infrared photopolymerization technology in deep photopolymerization, biomedicine, 3D printing and other fields. There are fewer surface groups inorganic upconverted particles, limiting the covalence of photoinitiators. Number of connections.
By constructing UCPs@MOFs composite particles, using MOFs to load photoinitiator, the fluorescence resonance energy transfer between UCPs and MOFs is achieved, the distance between photoinitiator and UCPs is shortened, the upconversion luminescence utilization rate is improved, and excitation is carried out under near-infrared light UV-visible light, improving photopolymerization rate and material performance.
It significantly improves the near-infrared photocuring speed and the mechanical properties of the material, improves the cross-linking degree and tensile fracture strength of the cured material, is suitable for the field of 3D printing, and improves the efficiency and accuracy of the photopolymerization system.
Smart Images

Figure CN119119328A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photopolymerization materials, and in particular to a near-infrared light-cured photoinitiator-loaded upconversion MOFs composite material and a preparation method thereof. Background Art
[0002] Upconversion particle-assisted near-infrared photopolymerization (UCAP) uses upconversion particles (UCPs) to convert the absorbed long-wave near-infrared light into short-wave ultraviolet-visible light, which then excites the ultraviolet photoinitiator molecules and initiates the polymerization reaction of the monomers. By simply physically adding UCPs to the photosensitive material, a flexible conversion from ultraviolet excitation to near-infrared excitation can be achieved, which makes UCAP compatible with almost all ultraviolet polymerization systems. It is precisely because of this advantage that UCAP has been widely used in deep photopolymerization, biomedicine, 3D printing, optical anti-counterfeiting and tissue repair in recent years. As a secondary light source dispersed in the polymerization system, UCPs need to convert as much near-infrared as possible into short-wave blue-violet light, but due to factors such as low absorption efficiency, many surface defects, and concentration quenching, the luminescence efficiency of UCPs is generally less than 2%. Therefore, the development of UCPs with stronger upconversion luminescence is of great significance to improving the polymerization rate of UCAP.
[0003] In order to solve the problem of low luminescence efficiency of upconversion particles UCPs, some researchers have shortened the distance between UCPs and photoinitiators by grafting photoinitiators (PI) on the surface of UCPs, and by limiting the photoinitiator within the effective area of fluorescence resonance energy transfer of upconversion particles UCPs, thereby improving the upconversion luminescence utilization rate of upconversion particles UCPs. However, due to the small number of surface groups of inorganic upconversion particles, the number of photoinitiators that can be covalently linked is limited, which limits their application in upconversion material assisted photopolymerization. Therefore, providing a new method to enhance the luminescence utilization rate of upconversion particles UCPs is an urgent problem to be solved by those skilled in the art.
[0004] Metal organic framework compounds (MOFs) are crystalline materials with an ordered porous structure formed by self-assembly of metal ions (or clusters) and organic ligands. They have the advantages of high specific surface area, multiple active sites and adjustable pore size, and show unique advantages in adsorption. Due to these advantages, MOFs have also been widely used in various fields such as catalytic separation, drug delivery, sensing and biomedical imaging.
[0005] Based on the above characteristics of MOFs materials and the advantages of UCPs such as adjustable emission wavelength, good photostability and long fluorescence lifetime, UCPs and MOFs are integrated to form a multifunctional heterostructure. UCPs can undergo upconversion fluorescence resonance energy transfer (FRET) with organic ligands in the MOFs framework or active components loaded in the MOFs pores, which can not only provide additional functions for UCPs, but also greatly broaden its application in various fields. The present invention uses UCPs as the core and MOFs as the satellite to construct a core-satellite structured UCPs@MOFs composite particle, and uses MOFs to load photoinitiators to achieve the integrated design of UCPs@MOF@PI, and explores the effect of this strategy on the photopolymerization rate and double bond conversion rate of UCAP, and verifies the application of this type of material in the field of 3D printing. Summary of the invention
[0006] Purpose of the invention: In view of the above problems existing in the prior art, the present invention provides a photoinitiator-loaded upconversion MOFs composite material for near-infrared light curing and a preparation method thereof. The present invention can increase the curing speed, improve the crosslinking degree and mechanical properties of the cured material through near-infrared light curing, and meet various use requirements of near-infrared light polymerization.
[0007] Technical solution: To achieve the above purpose, the technical solution adopted by the present invention is:
[0008] The first object of the present invention is to provide a photoinitiator-loaded upconversion MOFs composite material for near-infrared light curing, the composite material comprising upconversion particles UCPs, MOFs modified on the surface of UCPs, and photoinitiators loaded on the surface and pores of MOFs, recorded as UCPs@MOFs@PI composite particles, wherein the mass ratio of upconversion particles, MOFs and photoinitiators is 0.3-3: 0.1-1: 0.3-3. Optionally, in one embodiment of the present invention, the fluorescence emission band of the UCPs@MOFs@PI composite particles includes two bands, namely, an ultraviolet emission band in the range of 330-370nm, and a visible light emission band in the range of 430-480nm.
[0009] Optionally, in one embodiment of the present invention, the mass ratio of the upconversion particles, MOFs and photoinitiator is 0.3-3:0.1-0.75:0.3-3.
[0010] Optionally, in one embodiment of the present invention, the matrix material of the upconversion particle includes one or more of NaYF4, NaYbF4, NaGdF4, BaYF5, NaGdF4, LiYF4, doped with rare earth ions Er 3+ 、Tm 3+ 、Eu 3+、Ho 3+ One or more of .
[0011] Optionally, in one embodiment of the present invention, the MOFs include one or more of UiO-66, MOF-801, PCN-223, MIL-101, and ZIF-8.
[0012] Optionally, in one embodiment of the present invention, the photoinitiator includes one or more of bis-2,6-difluoro-3-pyrrophenyl titanocene, phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, 2-isopropylthioxanthone, camphorquinone, and [diethyl-(4-methoxybenzoyl)germanyl]-(4-methoxyphenyl)methanone.
[0013] The second object of the present invention is to provide a method for preparing a photoinitiator-loaded upconversion MOFs composite material for near-infrared light curing, comprising the following steps:
[0014] S1. Modify MOFs on UCPs: Disperse 0.3-3g of upconversion particles UCPs in 10-60mL of cyclohexane solution, add 10-60mL of polyvinyl pyrrolidone methanol solution and stir for 8-24h, then add 0.1-0.75g of MOFs and stir for 8-24h. Wash and centrifuge the obtained product particles, dry them in an oven at 60-90℃, and obtain UCPs@MOFs composite particles.
[0015] S2. UCPs@MOFs loaded with photoinitiator: Dissolve 0.3-3 g of photoinitiator in 10-80 mL of acetone, add the dried UCPs@MOFs composite particles, let stand for 24-48 hours, and then dry in an oven at 60-90°C to obtain UCPs@MOFs@PI composite particles.
[0016] Optionally, in one embodiment of the present invention, in step S1, the concentration of polyvinyl pyrrolidone in the methanol solution of polyvinyl pyrrolidone is 0.05-0.3 g / mL.
[0017] Optionally, in one embodiment of the present invention, in step S1, the centrifugal speed is 10000-12000 r / min.
[0018] Optionally, in one embodiment of the present invention, in step S1, the drying time is 24 to 48 hours.
[0019] Optionally, in one embodiment of the present invention, in step S2, the standing time is 24 to 48 hours.
[0020] Optionally, in one embodiment of the present invention, in step S2, the drying time is 24 to 48 hours.
[0021] Optionally, in one embodiment of the present invention, in step S1, the preparation method of the upconversion particles UCPs includes: weighing a total amount of 1-2 mmol of rare earth ion chloride into a 100-200 mL beaker, the molar fraction ratio of matrix ions to activator ions is 190-199:1-10, adding 20-40 mL of deionized water, stirring for 10-30 min, adding 1-4 mmol of tetraethylammonium oxalate and 10-40 mL of deionized water and stirring for 30-60 min, after the stirring is completed, adding 40-80 mL of deionized water and 12-24 mmol NaF, stirring for 1-2 h until the system becomes milky white, and then transferring the whole to a 100-500 mL polytetrafluoroethylene liner, the liner is placed in a hydrothermal reactor, sealed and placed in an oven, the temperature is set to 180°C to 220°C, the reaction is performed for 12h to 24h, the obtained product particles are washed and centrifuged, placed in an oven at 60-90°C, and dried.
[0022] The third object of the present invention is to provide an application of a photoinitiator-loaded upconversion MOFs composite material for near-infrared light curing in the field of near-infrared light curing.
[0023] The fourth object of the present invention is to provide a near-infrared light-curing material, which comprises a loaded photoinitiator up-conversion MOFs composite material and a resin system, wherein the near-infrared light-curing material comprises a loaded photoinitiator up-conversion MOFs composite material as described in any one of the above or prepared by any one of the above methods for near-infrared light curing.
[0024] Optionally, in one embodiment of the present invention, the resin system includes methacrylate oligomers, reactive diluents and epoxy resins.
[0025] Optionally, in one embodiment of the present invention, the methacrylate oligomer is one or more of polyurethane methacrylate, epoxy methacrylate, and polyester methacrylate.
[0026] Optionally, in one embodiment of the present invention, the epoxy resin is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, and bisphenol S epoxy resin; and / or preferably, the active diluent is one or more of o-phenylphenoxyethyl acrylate, 2-phenoxyethyl acrylate, isobornyl acrylate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, ethylene phthalate diacrylate, polyethylene glycol diacrylate, polypropylene glycol diacrylate, trimethylolpropane triacrylate, and pentaerythritol triacrylate.
[0027] Optionally, in one embodiment of the present invention, the raw materials of the near-infrared light-curable material include, by weight:
[0028]
[0029] Optionally, in one embodiment of the present invention, the heat release power of the near-infrared light-curing material is not less than 2 mW / mg.
[0030] Further optionally, in one embodiment of the present invention, the heat release power of the near-infrared light-curing material is 2 to 2.8 mW / mg.
[0031] Optionally, in one embodiment of the present invention, the double bond conversion rate of the near-infrared light-curable material is higher than 75%.
[0032] Further optionally, in one embodiment of the present invention, the double bond conversion rate of the near-infrared light-curable material is 75% to 85%.
[0033] Optionally, in one embodiment of the present invention, the glass transition temperature of the near-infrared light-curable material is higher than 92° C., and the crosslinking density is higher than 3.0×10 3 mol m -3 .
[0034] Further optionally, in one embodiment of the present invention, the glass transition temperature of the near-infrared light-curable material is 94 to 102° C., and the crosslinking density is higher than 3.1×10 3 ~3.3×10 3 mol m -3 .
[0035] Optionally, in one embodiment of the present invention, the tensile strength at break of the near-infrared light-curable material is higher than 30 MPa.
[0036] Further optionally, in one embodiment of the present invention, the tensile strength at break of the near-infrared light-curable material is 30 to 50 MPa.
[0037] The beneficial technical effects of the present invention are:
[0038] (1) In the present invention, near-infrared light has a stronger penetrating ability due to its small linear absorption and Rayleigh scattering. In addition, the up-conversion material can be excited by near-infrared light of a specific wavelength, and ultraviolet-visible light is generated after the up-conversion process. By utilizing this characteristic, the up-conversion nanoparticles can be used as countless built-in ultraviolet-visible light sources to solve the problem of rapid and deep curing of composite prepregs.
[0039] (2) The metal organic framework material MOFs in the present invention is a highly crystalline porous material formed by self-assembly of metal ions / metal clusters as nodes and organic ligands as connecting units. It has inherent structural advantages such as open pore structure, high porosity, and easy surface modification and functionalization, which is conducive to confining molecules within the pores for diffusion-controlled delivery.
[0040] (3) The multifunctional heterostructure formed by combining UCPs and MOFs in the present invention utilizes the large surface area and high active sites of MOFs to spatially confine the photoinitiator within the effective region of fluorescence resonance energy transfer of UCPs, thereby improving the upconversion luminescence utilization rate of UCPs.
[0041] (4) The present invention makes full use of the high penetration of near-infrared and the adsorption capacity of MOFs to form a heterostructure to link photoinitiators, thereby improving the upconversion utilization rate and curing speed and enhancing material performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 Schematic diagram of the preparation process of UCPs@ZIF-8@BAPO initiated near-infrared photopolymerization.
[0043] Figure 2 (a), (c) and (e) SEM images of Z-1, Z-2 and Z-3; (b), (d) and (f) statistical graphs of particle size distribution of Z-1, Z-2 and Z-3.
[0044] Figure 3 SEM photos: (a) upconversion particles; SEM images of Z-1 (b), Z-2 (c) and Z-3 (d) ZIF-8 composited with upconversion particles; (e) Zeta potential diagram of UCPs-PVP and ZIF-8.
[0045] Figure 4 (a) XRD pattern of UCPs@ZIF-8 composite particles and each component, (b) XRD pattern of UCPs@ZIF-8 with 2-Theta = 5°-15°.
[0046] Figure 5(a) Upconversion emission spectrum of UCPs@ZIF-8 composite particles under 980nm near-infrared light source excitation, (b) upconversion emission intensity of UZ-1, UZ-2 and UZ-3 at 345nm and 362nm.
[0047] Figure 6 Upconversion emission spectra of UCPs and UV absorption spectra of photoinitiator BAPO and ZIF-8.
[0048] Figure 7 The photo-DSC curves of weak UV polymerization reaction with different ZIF-8 addition amounts in nitrogen atmosphere.
[0049] Figure 8 The double bond conversion curves in the UCAP process, including (a) the effect of constructing integrated particles on UCAP, and (b) the effect of particles of different sizes of ZIF-8 and UCPs composites on UCAP.
[0050] Fig. 9 Schematic diagram of the relationship between the storage modulus and loss factor of UCAP cured material and temperature.
[0051] Fig.10 This is the influence of the composite system on the tensile fracture strength of the material.
[0052] Fig.11 Actual images of DIW printing of (a) UCPs system and (e) composite particle system; microscopic images of printed grids of (b), (c), (d) UCPs system and (f), (g), (h) composite particle system.
[0053] Fig.12 (a) Matrix structure printed by inks prepared by different systems, (b) heart-shaped grid structure and (c) tetrahedral grid structure printed by inks prepared by UZB system. DETAILED DESCRIPTION
[0054] Upconversion particles (UCPs) assisted near-infrared photopolymerization (UCAP) is an important photopolymerization technology, which uses UCPs to convert near-infrared light into ultraviolet light to achieve cross-linking and curing of photosensitive materials. However, the upconversion luminescence efficiency of UCPs is low, and photons will be lost during the propagation process inside the material, resulting in low energy transfer efficiency between upconversion materials and photoinitiators, which limits the wide application of this method. The present invention prepares a UCPs@metal organic framework (UCPs@ZIF-8) heterostructure material through electrostatic adsorption, and loads the photoinitiator with ZIF-8 to achieve the integration of UCPs, MOFs and photoinitiators to improve the curing efficiency of UCAP. The research results of the present invention show that the construction of composite particles can shorten the distance between UCPs and photoinitiators, improve the utilization rate of upconversion fluorescence, thereby obtaining a faster polymerization rate and a higher functional group conversion efficiency. This strategy was applied to near-infrared light-curable ink direct writing 3D printing, and the printed materials had better shape retention and higher precision, showing its application potential in the field of 3D printing. The cured materials obtained by this strategy have excellent mechanical properties, and the tensile strength increased from 25MPa to 47MPa.
[0055] The following examples are implemented based on the technical solutions of the invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following examples.
[0056] The experimental raw materials used in the examples of the present invention are as follows:
[0057] Tetraethoxylated bisphenol A diacrylate (EM2261): industrial grade, Changxing Chemical Materials (Suzhou) Co., Ltd.;
[0058] Photoinitiator bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (BAPO): industrial grade, Hubei Gurun Technology Co., Ltd.;
[0059] Ethylenediaminetetraacetic acid (EDTA): 98%, TCI;
[0060] Sodium fluoride (NaF): 99.99%, Sigma-Aldrich;
[0061] Ytterbium(III) chloride hexahydrate (YbCl3·6H2O): 99.9%, Sigma-Aldrich;
[0062] Thulium(III) chloride hexahydrate (TmCl3·6H2O): 99.99%, SigmaAldrich;
[0063] Zinc nitrate hexahydrate (Zn(NO3)2·6H2O): 99.9%, Sinopharm Chemical Reagent Co., Ltd.;
[0064] 2-Methylimidazole: 98%, Sinopharm Chemical Reagent Co., Ltd.;
[0065] Fumed silica A200, industrial grade, Evonik Specialty Chemicals (Shanghai) Co., Ltd.
[0066] The characterization method of the samples in the embodiments of the present invention and the experimental equipment used are as follows:
[0067] The crystal structure of the product was determined using an X-ray powder diffractometer (D8, Bruker AXS GmbH, Germany) (scanning speed: 8° / min, Cu K α1 ray );
[0068] The morphology of the samples was observed using a field emission scanning electron microscope (S-4800, Hitachi, Ltd., Japan);
[0069] The upconversion emission spectra of the composite particles were recorded using a fluorescence spectrometer (FS5, Edinburgh Instruments, UK);
[0070] A 980 nm continuous laser (FC-W-980H-50W, Changchun New Industries Optoelectronics Technology Co., Ltd.) was used as the irradiation light source;
[0071] The tensile properties of the light-cured samples were tested using a universal testing machine (5967X, ITW, USA);
[0072] The dynamic thermomechanical properties of the photocured samples were tested using a dynamic thermomechanical analyzer (DMA Q800, TA Company);
[0073] The curing process was characterized by using total reflection Fourier transform infrared spectroscopy (ATR-FTIR, Nicolet iS10 series, ThermoFisher)-rheometer platform (HAAKE MARS60), and the changes in the double bond characteristic absorption peak area were monitored in real time to characterize the conversion rate of the double bond during the resin curing process. The conversion rate calculation formula is shown in formula (1). The double bond characteristic peak interval selected is 1422-1394cm -1 , the reference peak interval is 1528-1481cm -1 ;
[0074] Conversion=(1-A t / A0)×100% (Formula 1)
[0075] Where: A0 is the ratio of the double bond absorption peak area before illumination to the reference peak area; A t It is the ratio of the double bond characteristic absorption peak area at time t of illumination to the reference peak area.
[0076] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0077] For the purpose of this specification and the appended claims, unless otherwise stated, all numbers expressing amounts, percentages or ratios and other numerical values used in this specification and the appended claims are understood to be modified in all cases by the term "about". In addition, all ranges disclosed herein are inclusive and independently combinable.
[0078] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0079] The present invention will be further described below in conjunction with the accompanying drawings and Examples. According to the following examples, the present invention can be better understood. However, it is easy for those skilled in the art to understand that the specific material ratios, process conditions and results described in the examples are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.
[0080] Example 1
[0081] A photoinitiator-loaded upconversion MOFs composite material, such as Figure 1 As shown, the preparation method comprises the following steps:
[0082] (1) Preparation of upconversion particles UCPs (NaYbF4:Tm 3+): Weigh a total of 1mmol of rare earth ion chloride (YbCl3·6H2O 1.99mmol and TmCl3·6H2O 0.01mmol) in a 100mL beaker, add 20mL of deionized water, stir for 10min, then add 2mmol of tetraethylammonium oxalate and stir for 30min. After stirring, add 50mL of deionized water and 24mmol of NaF, stir for 1h until the system turns milky white, then transfer the whole to a 100mL polytetrafluoroethylene liner, put the liner into a hydrothermal reactor, seal it and put it in an oven, set the temperature to 180℃, react for 24h, wash the obtained product particles with deionized water three times, wash them with ethanol three times, centrifuge at 3000rpm, put them in a 70℃ oven for 12h, dry them with ethanol and store them for later use to obtain UCPs.
[0083] (2) Synthesis of ZIF-8
[0084] Three ZIF-8 particles of different sizes were prepared according to the method reported in the literature.
[0085] First, Zn(NO3)2·6H2O was dissolved in 10 mL of deionized water, and then 2-methylimidazole was dissolved in 90 mL of deionized water. The amount of 2-methylimidazole was changed according to Table 1. The two aqueous solutions were then mixed at room temperature to quickly form a white precipitate. The mixture was aged at room temperature for 24 h, and then the white precipitate was centrifuged at 10000 r / min, washed three times with deionized water, and finally dried in a vacuum oven at 60°C for 24 h. The obtained ZIF-8 were recorded as Z-1, Z-2, and Z-3.
[0086] Table 1 Preparation amount of ZIF-8
[0087]
[0088] (3) Modification of MOFs on UCPs: 0.3 g of upconversion particles UCPs were dispersed in 10 mL of ethanol solution, and then 20 mL of ethanol solution containing 1 g of polyvinyl pyrrolidone was added and stirred for 12 h. PVP-coated UCPs were added to a beaker, and then 0-0.375 g of MOFs were added and stirred for 24 h. The obtained product was washed, centrifuged, and placed in a 70 °C oven. After drying with ethanol, it was stored for later use.
[0089] (4) Upconversion MOFs loaded with photoinitiator: 0.4 g of photoinitiator BAPO was dissolved in 10 mL of acetone, and then 0.5 g of dried MOFs-modified upconversion UCPs particles were added. After standing for 24 h, the particles were dried in a 70 °C oven for later use.
[0090] Test Case
[0091] (1) Morphology and phase analysis of UCPs@ZIF-8
[0092] like Figure 2 As shown, the size of ZIF-8 particles prepared in step (2) of Example 1 can be controlled by adjusting the ratio of metal ions to organic ligands. Excessive 2-methylimidazole ligands can increase the nucleation rate, rapidly nucleate to obtain a large number of crystal nuclei, shorten the crystal growth stage, and thus obtain small-sized particles. Figure 2 As shown in (a) and (b), when the molar ratio of zinc ions and 2-methylimidazole is 1:40, the ZIF-8 particles are spherical with a size of about 800 nm. When the molar ratio is 1:60 and 1:80, the ZIF-8 particles are rhombic dodecahedrons with average particle sizes of 250 nm and 200 nm, respectively.
[0093] The SEM images of upconversion particles UCPs prepared by hydrothermal method are shown in Figure 2. Figure 3 As shown in (a), the upconversion particles present a uniform hexagonal morphology, with an average diameter of 3 μm and an average length of 15 μm. The upconversion inorganic particles were modified with surfactant polyvinyl pyrrolidone. From the Zeta potential diagram, it can be seen that the surface of the modified UCPs is negatively charged, and electrostatic adsorption can occur with the positively charged ZIF-8 particles on the surface, as shown in Figure 2. Figure 3 As shown in (b), (c), and (d), ZIF-8 particles were successfully loaded on the surface of UCPs to form core-satellite structured composite particles. Due to their small size, the 200 nm ZIF-8 particles partially agglomerated, and the composite effect was lower than that of the other two larger sizes of ZIF-8.
[0094] XRD was used to characterize the crystal structure of the composite heterostructure UCPs@ZIF-8 and its components. Figure 4 The diffraction peak positions of the upconversion particles UCPs are consistent with the standard card PDF#27-1427 of β-phase NaYbF4:Tm. The metal-organic framework ZIF-8 is well crystallized, with obvious diffraction peaks at 2θ=7.3°, 10.3°, 12.8°, 14.9°, 16.6°, 18.0°, 21.9°, 24.6° and 26.7°, which are respectively attributed to the (011), (002), (112), (022), (013), (222), (233), (134) and (044) crystal planes of ZIF-8 particles. The diffraction peaks at 2θ=7.3°, 10.3°, and 12.8° of the prepared heterostructure UCPs@ZIF-8 correspond to the (011), (002), and (112) crystal planes of the ZIF-8 particles, which also indicates the successful preparation of the heterostructure UCPs@ZIF-8.
[0095] (2) Fluorescence properties of UCPs@ZIF-8
[0096] Figure 5 The upconversion emission spectra of UCPs and UCPs@ZIF-8 heterostructures under 980nm near-infrared light excitation clearly show that they belong to the lanthanide ion Tm 3+ The characteristic emission peaks of the two emission peaks located at 345nm and 362nm in the ultraviolet band belong to 1 I6→ 3 F4 and 1 D2→ 3 The transition of H6, the two emission peaks at 451nm and 476nm in the blue light band belong to 1 D2→ 3 F4 and 1 G4→ 3 H6, the emission peak at 650nm in the red light band belongs to 1 G4→ 3 H4 transition. Compare the 345nm and 362nm emission lights mainly used by the photoinitiator, such as Figure 5 As shown in (b), compared with the luminescence intensity of pure UCPs particles, the upconversion luminescence intensity of heterostructure composite particles UCPs@ZIF-8 is reduced. The upconversion luminescence intensity of UZ-1, UZ-2 and UZ-3 is reduced by 36.1%, 26.7% and 47.6% respectively compared with pure UCPs particles. As the size of ZIF-8 particles decreases, the upconversion luminescence intensity first increases and then decreases. UZ-2 obtains the highest luminescence intensity among the composite particles. The introduction of ZIF-8 partially covers the surface of UCPs, affecting the intensity of its upconversion luminescence. The smaller the size of ZIF-8 particles and the more uniform the dispersion, the smaller the effect on the upconversion luminescence intensity of UCPs.
[0097] (3) Effect of composite particles UCPs@ZIF-8@BAPO on the polymerization behavior of UCAP
[0098] The matching of the absorption spectrum of the photoinitiator and the emission spectrum of UCPs in the UCAP system is very important and determines the initiation efficiency of UCAP. Figure 6 As shown, the fluorescence emission band of the UCPs synthesized in the present embodiment is mainly located in two bands, namely the ultraviolet emission band located in the interval of 330-370nm, and the visible light emission band located in the interval of 430-480nm, and the main absorption peak of the selected photoinitiator BAPO is located between 300-400nm, which shows that the ultraviolet light emitted by UCPs upconversion can cause the initiator BAPO molecular cracking and thus realize the light initiation process. The introduced ZIF-8 particles have no absorption in the interval of 300-600nm, avoiding the decline of the initiation efficiency of the system caused by the ultraviolet absorption of the ZIF-8 particles. Therefore, the heterostructured UCPs@ZIF-8 composite particles are expected to realize the efficient initiation of the photoinitiator BAPO.
[0099] The embodiment of the present invention uses EM2261 photosensitive monomer to study the polymerization behavior of the UCAP system. The photo-DSC test can characterize the change of heat flow during the polymerization process. The magnitude of the heat release power is related to the speed of the polymerization reaction. Figure 7 This is the DSC curve of weak ultraviolet polymerization reaction in nitrogen atmosphere. It simulates the ultraviolet light emitted by UCPs in the system after absorbing near-infrared light. With the opening of the ultraviolet light source, the polymerization reaction occurs, and then the polymerization exothermic power increases rapidly. In the ultraviolet polymerization system, the maximum exothermic power increases first and then decreases with the increase of the amount of ZIF-8 added. When the amount of ZIF-8 added is 0.25wt% of the polymerization system, the maximum exothermic power reaches the highest, which is 2.65mW / mg, which is 38.7% higher than that of the pure UCPs system. The results show that the addition of ZIF-8 particles in the system can accelerate the polymerization reaction and increase the polymerization rate. However, excessive ZIF-8 particles will cause the maximum exothermic power to decrease and the polymerization rate to decrease. This may be because a large amount of ZIF-8 particles aggravates the light scattering in the system and affects the light initiation efficiency. Therefore. The subsequent experiments will use this amount of ZIF-8.
[0100] Figure 8 This is the time curve of double bond conversion rate of EM2261 in different near-infrared light initiation systems. Figure 8 (a) Comparison of the photopolymerization rate and the final double bond conversion rate when UCPs exist alone and when ZIF-8 particles are added in the UCAP system. It can be seen that the polymerization rate is increased when ZIF-8 particles are added, and the final double bond conversion rate is increased from 75% to nearly 80%. The reason may be that the catalytic effect of ZIF-8 particles leads to more active species in the early stage of polymerization. This result is consistent with the results of DSC test. The addition of heterogeneous structure UCPs@ZIF-8 can also increase the polymerization rate and double bond conversion rate of the system, but it is slightly lower than the system with only ZIF-8 particles. This may be because the heterogeneous structure of the composite particles reduces the upconversion luminescence intensity of UCPs. The group of composite particles UCPs@ZIF-8@BAPO adsorbed with photoinitiator achieved the highest polymerization rate and a final conversion rate of 85%. This is because the large specific surface area and high porosity of ZIF-8 in the heterogeneous structure UCPs@ZIF-8 can enrich the photoinitiator molecules on the inner and outer surfaces of its pores, and after being dispersed in the monomer, the uneven distribution of photoinitiators in the system can still be guaranteed, and there are more photoinitiators close to UCPs. Therefore, the photoinitiators enriched around MOF will be preferentially initiated, ensuring that the distance between the photoinitiator and UCPs is within the range where Förster fluorescence resonance energy transfer can occur, and ultimately improving the utilization rate of UCPs upconversion luminescence and thus the polymerization rate and final conversion rate of the system. The size of the composite component ZIF-8 will also have an impact on the UCAP process, such as Figure 8As shown in (b), the UZB-2 component has the fastest polymerization rate and double bond conversion rate, which is attributed to the fact that it has the highest upconversion luminescence intensity in the composite particles while shortening the distance between the initiator and UCPs and improving the luminescence utilization rate, thus achieving the best polymerization effect.
[0101] (4) Effect of composite particles UCPs@ZIF-8@BAPO on the mechanical properties of materials
[0102] The effect of adding UCPs@ZIF-8@BAPO composite particles on the dynamic thermomechanical properties of UCAP cured materials was tested by DMA. The functional relationship between storage modulus and loss factor and temperature is shown in Figure 2. Fig. 9 The corresponding data are summarized in Table 2. It can be seen that the storage modulus of the UCAP cured material decreases with increasing temperature, which is attributed to the softening of the polymer molecular chain as the temperature increases. The temperature corresponding to the maximum value of the loss tangent is regarded as the glass transition temperature (T g ), the crosslinking density ν can be calculated by referring to the rubber elasticity theory through the following formula:
[0103]
[0104] The original UCAP system without ZIF-8 Non-ZIF cured material T g The crosslinking density is 3.3×10 3 mol m -3 . T of UZB-1 system, UZB-2 and UZB-3 system curing materials g The crosslink densities were 3.2×10 3 mol m -3 , 3.3×10 3 mol m -3 and 3.1×10 3 mol m -3 The integration strategy of UZB composite particles improves the curing speed of the material and shortens the time before the material reaches the gel point. Therefore, the UZB system can make the material have a higher double bond conversion rate when it reaches the gel point, thereby improving the crosslinking density of the material. At the same time, the average chain length between adjacent crosslinking points is reduced, which hinders the movement of molecular segments and increases the glass transition temperature. This shows that UZB composite particles can not only improve the curing rate of the UCAP system, but also enable the UCAP-cured material to obtain better dynamic thermomechanical properties.
[0105] Table 2 Thermomechanical properties of cured materials
[0106]
[0107] In order to explore the effect of the integration of composite particles UCPs@ZIF-8@BAPO on the properties of the cured material, the tensile properties of the cured material were tested, such as Fig. 9 As shown. The tensile strength of the materials obtained after UCAP of the composite particles is improved compared with the original UCAP system, and it first increases and then decreases with the increase of ZIF-8 size. The tensile fracture strength of the material cured by the original UCAP system is 25.8MPa, and the tensile fracture strength of the materials cured by UZB-1, UZB-2 and UZB-3 systems are 33.9MPa, 47.3MPa and 31.5MPa, which are 31.4%, 83.3% and 22.0% higher than the tensile fracture strength of 25.8MPa of the materials obtained by the original UCAP system, respectively. This is attributed to the higher cross-linking density of the component materials, which further shows that the integrated design of the composite particles is not only conducive to improving the curing rate and double bond conversion rate, but also ultimately improves the mechanical properties of the materials.
[0108] Application example: Application of composite particles UCPs@ZIF-8@BAPO in 3D printing
[0109] Direct ink writing (DIW) is a light-curing 3D printing technology based on extrusion molding, which has the advantages of fast curing speed, good surface quality, high utilization of raw materials, and simple and easy printing. Compared with the DIW strategy of deposition before curing, the photopolymerization-driven real-time curing DIW strategy can relax rheological restrictions and facilitate high-speed printing.
[0110] The integrated construction of UCPs@ZIF-8@BAPO composite particles can enable the printing ink to achieve a higher curing rate in terms of kinetics and better match the printing speed. Fig.11(a) and (e) are three-layer square grids directly written by real-time curing DIW ink using UCPs alone and UCPs@ZIF-8@BAPO composite particle integration strategy, respectively. A 600μm nozzle is used for DIW printing. The line width of the component grid of the traditional UCAP system without adding MOFs is about 613.5μm. This is because the slow in-situ curing rate during the DIW process causes the ink to not cure quickly and maintain a cylindrical shape during extrusion. The line width of the upper grid is about 621.7±4.6μm, and the line width of the lower grid is 605.3±5.3μm, with a difference of about 16.4μm, indicating that the lines printed by this system are uneven and have low precision. The line width of the component grid using the UZB system is approximately 550.3μm, the line width of the upper grid is 554.1±0.8μm, and the line width of the lower grid is approximately 546.5±1.3μm. The line width difference between the upper and lower layers is smaller, which is 7.6μm. The higher rate advantage of the UZB system leads to more complete in-situ curing, which makes the prints more uniform in all parts and more beautiful in shape, similar to the target structure. Fig.12 (a) shows the array structure printed by UCAP. The 3D printed vertical array prepared by UCAP without adding ZIF will tilt during the printing process, which is attributed to the difficulty in matching the slower curing rate with the printing rate, while the UZB array can obtain lines perpendicular to the plane due to the faster curing rate. Fig.12 (b) and (c) show the heart-shaped grid structure and tetrahedral pyramid structure printed by UZB-based UCAP, indicating that the integrated construction of composite particles improves the DIW printing accuracy and consistency with the target structure on the basis of improving the real-time curing rate, providing a reference strategy for the improvement of DIW printing in the future.
[0111] The present invention can improve the efficiency of upconversion particle-assisted photopolymerization by changing the combination mode of UCPs, MOFs and photoinitiators, thereby solving the defect of low quantum yield of upconversion particles and making upconversion particle-assisted photopolymerization more convenient, efficient and more widely applicable.
[0112] The present invention constructs a UCPs@ZIF-8@BAPO composite particle, introduces the heterogeneous structure of UCPs@ZIF-8, combines the upconversion particle, which is an important component in the upconversion particle-assisted photopolymerization, with a photoinitiator, shortens the distance between UCPs and the photoinitiator, improves the luminescence utilization rate of the upconversion particle, reduces energy loss through the fluorescence resonance energy transfer mechanism, and achieves a confined effect by introducing MOF, thereby increasing the local photoinitiator concentration of the system. Under near-infrared light irradiation, the active free radicals generated by the composite system are more effective in initiating free radical polymerization than the physical mixed photoinitiator system. The construction of the composite particle is conducive to the release of the shrinkage stress of the corresponding polymerization system, and the glass transition temperature and crosslinking density of the cured material are increased by 10.1% and 10.0%, respectively, which gives the material higher tensile properties, from 25.8MPa to 47.3MPa. Near-infrared photopolymerization-assisted ink direct writing printing was completed using composite particles, and the line error obtained by printing was reduced from 16.4μm to 7.6μm compared with the system involving pure UCPs, which improved the shape retention and printing accuracy of real-time curing DIW. This strategy can effectively promote the development of NIR-DIW application technology.
[0113] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A photoinitiator-loaded upconversion MOFs composite material for near-infrared light curing, characterized in that: The composite material includes upconversion particles UCPs, MOFs modified on the surface of UCPs, and photoinitiators loaded on the surface and pores of MOFs, which are recorded as UCPs@MOFs@PI composite particles, wherein the mass ratio of upconversion particles, MOFs and photoinitiators is 0.3-3:0.1-1:0.3-3.
2. The photoinitiator-loaded upconversion MOFs composite material for near-infrared light curing according to claim 1, characterized in that: The fluorescence emission band of the UCPs@MOFs@PI composite particles includes two bands, namely, an ultraviolet emission band located in the range of 330-370nm, and a visible light emission band located in the range of 430-480nm; and / or The mass ratio of the up-conversion particles, MOFs and photoinitiator is 0.3-3:0.1-0.75:0.3-3.
3. The photoinitiator-loaded upconversion MOFs composite material for near-infrared light curing according to claim 1, characterized in that: The matrix material of the up-conversion particle includes one or more of NaYF4, NaYbF4, NaGdF4, BaYF5, NaGdF4, LiYF4, doped with rare earth ions Er 3+ 、Tm 3+ 、Eu 3+ 、Ho 3+ One or more of .
4. The photoinitiator-loaded upconversion MOFs composite material for near-infrared light curing according to claim 1, characterized in that: The MOFs include one or more of UiO-66, MOF-801, PCN-223, MIL-101, and ZIF-8.
5. The photoinitiator-loaded upconversion MOFs composite material for near-infrared light curing according to claim 1, characterized in that: The photoinitiator includes one or more of bis-2,6-difluoro-3-pyrrolephenyl titanocene, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, 2-isopropylthioxanthone, camphorquinone, and [diethyl-(4-methoxybenzoyl)germanyl]-(4-methoxyphenyl)methanone.
6. A method for preparing a photoinitiator-loaded upconversion MOFs composite material for near-infrared light curing, characterized in that: The steps include: S1. Modify MOFs on UCPs: Disperse 0.3-3g of upconversion particles UCPs in 10-60mL of ethanol solution, add 10-60mL of polyvinyl pyrrolidone ethanol solution and stir for 8-24h, then add 0.1-0.75g of MOFs and stir for 8-24h. Wash and centrifuge the obtained product particles, dry them in an oven at 60-90℃, and obtain UCPs@MOFs composite particles. S2. UCPs@MOFs loaded with photoinitiator: dissolve 0.3-3 g of photoinitiator in 10-80 mL of acetone, add 0.4-4 g of dried UCPs@MOFs composite particles, let stand for 24-48 hours, and then dry in an oven at 60-90°C to obtain UCPs@MOFs@PI composite particles.
7. The method according to claim 6, characterized in that In step S1, the concentration of polyvinyl pyrrolidone in the ethanol solution of polyvinyl pyrrolidone is 0.05-0.3 g / mL; and / or Preferably, in step S1, the centrifugal speed is 10000-12000 r / min; and / or Preferably, in step S1, the drying time is 24 to 48 hours; and / or Preferably, in step S2, the standing time is 24 to 48 hours; and / or Preferably, in step S2, the drying time is 24 to 48 hours; and / or Preferably, in step S1, the preparation method of the upconversion particles UCPs includes: weighing a total amount of 1-2 mmol of rare earth ion chloride into a 100-200 mL beaker, the molar fraction ratio of the matrix ion to the activator ion is 190-199:1-10, then adding 20-40 mL of deionized water, stirring for 10-30 min, then adding 1-4 mmol of tetraethylammonium oxalate and 10-40 mL of deionized water and stirring for 30-60 min, after the stirring is completed, adding 40-80 mL of deionized water and 12-24 mmol of NaF, stirring for 1-2 h until the system appears milky white, and then transferring the whole to a 100-500 mL polytetrafluoroethylene liner, the liner is placed in a hydrothermal reactor, sealed and placed in an oven, the temperature is set to 180-220 ° C, the reaction is 12h to 24h, the obtained product particles are washed and centrifuged, placed in a 60-90 ° C oven, and dried.
8. Application of upconversion MOFs composite materials loaded with photoinitiators for near-infrared photocuring in the field of near-infrared photocuring.
9. A near-infrared light-curing material, characterized in that: The near-infrared light-curing material includes a loaded photoinitiator up-conversion MOFs composite material and a resin system, wherein the near-infrared light-curing material includes a loaded photoinitiator up-conversion MOFs composite material, which is a loaded photoinitiator up-conversion MOFs composite material for near-infrared light curing as described in any one of claims 1-5 or prepared by the method described in any one of claims 6-7.
10. The near-infrared light-curable material according to claim 9, characterized in that: The resin system comprises methacrylate oligomer, reactive diluent and epoxy resin, Preferably, the methacrylate oligomer is one or more of polyurethane methacrylate, epoxy methacrylate, polyester methacrylate; and / or Preferably, the epoxy resin is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, and bisphenol S epoxy resin; and / or preferably, the reactive diluent is one or more of o-phenylphenoxyethyl acrylate, 2-phenoxyethyl acrylate, isobornyl acrylate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, ethylene phthalate diacrylate, polyethylene glycol diacrylate, polypropylene glycol diacrylate, trimethylolpropane triacrylate, and pentaerythritol triacrylate; and / or Preferably, the raw materials of the near-infrared light-curable material include, by weight: Preferably, the heat release power of the near-infrared light-curing material is not less than 2 mW / mg, and further, the heat release power of the near-infrared light-curing material is 2 to 2.8 mW / mg; and / or Preferably, the double bond conversion rate of the near-infrared light-curable material is higher than 75%, and further, the double bond conversion rate of the near-infrared light-curable material is 75% to 85%; and / or Preferably, the glass transition temperature of the near-infrared light-curable material is higher than 92°C, and the cross-linking density is higher than 3.0×10 3 mol m -3 Furthermore, the glass transition temperature of the near-infrared light-curable material is 94-102°C, and the cross-linking density is higher than 3.1×10 3 ~3.3×10 3 mol m -3 ; and / or Preferably, the tensile strength at break of the near-infrared light-curable material is higher than 30 MPa. Furthermore, the tensile strength at break of the near-infrared light-curable material is 30 to 50 MPa.
Citation Information
Patent Citations
Photoinitiator compound based on up-conversion materials as well as preparation method and application of photoinitiator compound
CN109232776A
Preparation method and application of up-conversion-metal organic framework molecularly imprinted catalytic material
CN111644204A
Core-shell upconversion MOFs photosensitive composite material, preparation method and application thereof
CN113230401A
Stereo-configuration near-infrared light initiator as well as preparation method and application thereof
CN114891215A
Co-MOF-added photocuring gunpowder and preparation method thereof
CN115806456A
Cited By
Method for preparing trichloromethoxybenzene through near-infrared light radiation
CN117088761A
Modified difficult-to-cure ceramic powder based on metal organic framework coating as well as preparation method and application of modified difficult-to-cure ceramic powder
CN119751086A
